Drug-Coated versus Uncoated Balloon for Side Branch Protection in Coronary Bifurcation Lesions Treated with Provisional Stenting Using Drug-Eluting Stents: A Meta-analysis - Zhi-Ming Jiang; Le Liu (International Journal of Clinical Practice)
Background. Provisional stenting using drug-eluting stents (DES) has become the preferred treatment for coronary bifurcation lesions (CBLs). We performed a meta-analysis to compare the effects of side branch (SB) protection using a drug-coated balloon (DCB) versus an uncoated balloon (UCB) during the procedure. Methods. Relevant randomized and nonrandomized studies were identified by searching the Medline, Embase, Web of Science, Wanfang, and CNKI databases. We used a random-effect model to pool the data by incorporating the heterogeneity between the included studies. Results. Overall, 803 patients with CBLs treated with provisional stenting using DES were included from seven studies. With a follow-up duration of 6 to 12 months, SB protection with DCB was associated with a lower degree of postoperative diameter stenosis (mean difference (MD): −11.35%, 95% confidence interval (CI): −14.17 to−8.53, p<0.001; I2 = 0%) and less late lumen loss (MD: −0.19 mm, 95% CI:−0.28 to−0.10, p<0.001; I2 = 69%) of SB compared to those with UCB. Moreover, SB protection with DCB was associated with reduced risks of target lesion revascularization (risk ratio [RR]: 0.49, 95% CI: 0.27 to 0.88, p=0.02; I2 = 0%) and major adverse cardiovascular events (RR: 0.42, 95% CI: 0.27 to 0.66, p<0.01; I2 = 0%). Subgroup analysis according to the study design showed similar results. Conclusions. For patients with CBL treated with provisional stenting using DES, SB protection with DCB was associated with better angiographic and clinical outcomes than those with UCB.